Central Bank Transparency and Financial Stability: Measurement, Determinants and Effects - Roman Horváth; Dan Vako (FIW - Research Centre International Economics, 2013)
We develop a comprehensive index of the transparency of central banks regarding their policy framework to promote financial stability for 110 countries from 2000 to 2011 and examine the determinants and effects of this transparency. We find that the degree of transparency increased in the 2000s, though it still varied greatly across the countries in our study. Our regression results suggest that more developed countries exhibit greater transparency, that episodes of high financial stress have a negative effect on transparency and that the legal origin matters, too. Importantly, we find that transparency regarding the level of financial stability is strongly affected by monetary policy transparency. The central banks that have a transparent monetary policy are more likely to show increased transparency in their framework for financial stability. Our results also suggest a non-linear effect of central bank financial stability transparency on financial stress. Unless the financial sector experiences severe distress, greater transparency is beneficial for financial stability.
Keywords: E52; E58; 330; financial stability; transparency; central banks